The Effect of Promotions and Prices on Customer Satisfaction on The Gojek Application (Go-Ride) (Study of LP3I Banten Students) - Karlina, Yayuk; Eman Diantoro; Ahmad Najiyullah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aimed to investigate whether promotions and pricing significantly influence customer satisfaction with the Gojek application among LP3I Banten students. A quantitative research approach was employed, collecting data from a convenience sample of 80 Gojek users. Statistical analysis was conducted using SPSS 22 software, including correlation and regression analysis. The findings indicate that while promotional efforts did not have a significant effect on customer satisfaction, price did have a significant influence. Furthermore, the results demonstrate that both promotions and prices collectively had a significant impact on customer satisfaction, both in partial and simultaneous analyses